2018
DOI: 10.12988/asms.2018.863
|View full text |Cite
|
Sign up to set email alerts
|

Climate indicators and the impact on morbidity and mortality of acute respiratory infections

Abstract: The fire incidences in Campo Grande have been a serious environmental problem. Therefore, this study is aimed at studying the trend of acute respiratory infections (IRA) from the year 2011 to 2017 and to correlate it with precipitation, wind speed, relative humidity, maximum and minimum temperatures, surface ozone concentration, optical depth, index of clarity and the number of outbreaks of fires. IRA records were obtained through DATASUS; the record of burn outbreaks at the National Institute for Space Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…The lower the levels of air pollution, the better the health of the population with cardiovascular and respiratory diseases, both in the long and short term. Therefore, it is very important to constantly monitor air quality to assess the impact of pollutants on human health (Souza and Da Silva Santos 2020 ; Souza et al 2018a , 2018b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower the levels of air pollution, the better the health of the population with cardiovascular and respiratory diseases, both in the long and short term. Therefore, it is very important to constantly monitor air quality to assess the impact of pollutants on human health (Souza and Da Silva Santos 2020 ; Souza et al 2018a , 2018b ).…”
Section: Resultsmentioning
confidence: 99%
“…The lower the levels of air pollution, the better the health of the population with cardiovascular and respiratory diseases, both in the long and short term. Therefore, it is very important to constantly monitor air quality to assess the impact of pollutants on human health (Souza and Da Silva Santos 2020;Souza et al 2018aSouza et al , 2018b. This study will focus on the state of Mato Grosso do Sul (MS), in the Midwest region of Brazil, based on the largest cities (Campo Grande, Dourados, Três Lagoas, Corumbá, Coxim, Porto Murtinho, Ponta Porã, and Chapadão do Sul) (IBGE 2021).…”
Section: Spatial Distribution Of Air Pollutantsmentioning
confidence: 99%
“…Sensitive and vulnerable groups, such as pregnant women, children, the elderly, and those who already suffer from respiratory illnesses and other serious diseases, or from low-income groups, are especially affected by climatic variation. Studies have shown that the number of respiratory diseases in children and the elderly increases due to the higher concentrations of air pollution (Souza, et al, 2018c;Souza, et al, 2018d;Souza, et al, 2017;Santos, et al, 2017;Braga, et al, 1999;Braga, et al, 2001;Viegi, et al, 2009). According to these studies, children are more susceptible because they need twice the amount of air inhaled by adults, and the elderly are more affected because of their weakened immune and respiratory systems and have been exposed to a large amount of air pollution in all your life.…”
Section: Introductionmentioning
confidence: 99%
“…Nas pesquisas ligadas aos problemas ambientais, variáveis climáticas como umidade relativa do ar, temperatura e a precipitação pluviométrica têm sido amplamente estudadas e relacionadas à saúde da população (Peng, Xiao-Ming, & Qi-Yong, 2020;Santos et al, 2017;Sobral et al, 2020;Souza et al, 2018). Diante disso, o estudo de radiação solar se faz importante, pois a radiação solar está ligada as variações sazonais da temperatura (Spokas, 2006).…”
Section: Introductionunclassified